Epidemiological and clinical characteristics of COVID-19 patients in Nantong, China - Renfei Lu; Jianru Qin; Yan Wu; Jian Wang; Shengyong Huang; Lijun Tian; Tao Zhang; Xiuming Wu; Songping Huang; Xia Jin; Chiyu Zhang (Journal of Infection in Developing Countries)
Introduction: COVID-19 is a newly emerging life-threatening respiratory disease caused by a newly identified coronavirus SARS-CoV-2.